Inibição da corrosão de aço carbono 4340 em biodiesel de babaçu por extrato etanólico de folhas de Myracrodruon urundeuva allemão - Silva, Lucas Costa da (2024)
In this work, the potential of the ethanolic extract of leaves of aroeira-do-sertão, Myracrodruon urundeuva fr, was investigated. all., and the synthetic antioxidant trolox as corrosion inhibitors of carbon steel 4340 in babassu biodiesel (B100). Static immersion tests were conducted in duplicate at 45 °C for 108 days (2,592 hours). The analysis of the corrosive behavior was carried out mainly through measurements of mass loss and corrosion inhibition efficiency of the extract and trolox. Furthermore, after the gravimetric tests, the surface morphology of the carbon steel samples was evaluated by scanning electron microscopy. The composition of the extract was analyzed by Fourier Transform Infrared Spectroscopy (FTIR). Based on the experimental conditions, the results suggest that the use of the ethanolic extract of aroeira-do-sertão leaves and trolox significantly reduced metallic corrosion compared to samples subjected to immersion in non-additivated biodiesel. The extract showed an inhibition efficiency of 89%, which is in accordance with literature data, while trolox resulted in only 27.9% efficiency. Therefore, the ethanolic extract of aroeira-do-sertão leaves proved to be an efficient metallic corrosion inhibitor additive for babassu biodiesel with regard to inhibiting the corrosion of 4340 carbon steel.